Exploring spiritual education in the Chinese context: concepts, objectives and methods - Yanmei, Zhao; Muhamad, Mohd Mokhtar; Mustakim, Siti Salina (Human Resource Management Academic Research Society (HRMARS), 2023)
The purpose of this paper is to explore in depth the development of spiritual education in China, focusing on analyzing its concepts, objectives, and implementation methods. As an educational approach to cultivating inner emotional wisdom and moral awareness, spiritual education is gradually emerging in Chinese academics. As an educational model focusing on the individual's inner growth, emotional cognition, and meaning of life, it highlights the cultivation of inspirational wisdom, moral values, and social responsibility. It integrates traditional cultural values with modern educational requirements. It is essential to supplement formal subject education, promote all-round development, and foster a sense of social responsibility. The methods and strategies for conducting spiritual education cover various dimensions, including curriculum development, educational activities, teacher training, and student participation. These methods and techniques can help guide students to emotional expression, inner growth, emotional intelligence, and holistic development. Through a systematic review approach, this paper presents a comprehensive picture of spiritual education's status and significance in China. It provides valuable guidance for future educational practice and research to cultivate more emotionally intelligent and socially responsible students.